TEST KIT UNTUK ANALISIS SIANIDA DALAM KETELA POHON BERDASARKAN PEMBENTUKAN HIDRINDANTIN - Sulistyarti, Hermin; Kusumawardhani, Nury; Zulfah, Novy Lailatuz; Cahyani, Yulia Dwi; Fahriyani, Hilda Emilia; Milda, Balqis (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Cyanide is a highly toxic substance, which causes high number of poisoning by cyanide in a variety of foodstuffs; therefore the availability of test kits as fast and easy tool for analyzing cyanide is extremely demanded. The proposed cyanide test kit is developed based on the reaction of cyanide and nynhidrine to form a blue hydrindantin under strong basic solution. Cyanide test kit was optimized toward the λ maximum, pH, stability time of complex and concentration of nynhidrine. Optimization of maximum λ was done by measuring absorbance using visible spectrophotometer at range λ 560-620 nm. Optimization of pH was done by conditioning hydrindantine complex using NaOH solution to obtain pH of 9-14. Optimization of stability time of complex was done by monitoring complex under time range 0-120 minutes. The optimization of ninhydrin concentration was performed by varying the concentration of ninhydrin in range 0.5 to 3.5%. The results showed that the optimum conditions were: λ 590 nm, pH 12, the stability time of complex of 30 minutes, and concentration of ninhydrin of 1%. Test kit can determine cyanide at the range 1-10 ppm. test kit has been validated and applied for measuring cyanide in cassava with reliable results. Keywords: nynhidrin, hidrindantin, cyanide, test kit, cassava